One Up : Creativity, Competition, and the Global Business of video games - Van Dreunen, Joost, ....- (New York : Colombia University Press, 2020)
What explains the massive worldwide success of video games such as Fortnite, Minecraft, and Pokémon Go? Game companies and their popularity are poorly understood and often ignored from the standpoint of traditional business strategy. Yet this industry generates billions in revenue by thinking creatively about digital distribution, free-to-play content, and phenomena like e-sports and live streaming. What lessons can we draw from its major successes and failures about the future of entertainment? One Up offers a pioneering empirical analysis of innovation and strategy in the video game industry to explain how it has evolved from a fringe activity to become a mainstream form of entertainment. Joost van Dreunen, a widely recognized industry expert with over twenty years of experience, analyzes how game makers, publishers, and platform holders have tackled strategic challenges to make the video game industry what it is today. Using more than three decades of rigorously compiled industry data, he demonstrates that video game companies flourish when they bring the same level of creativity to business strategy that they bring to game design. Filled with case studies of companies such as Activision Blizzard, Apple, Electronic Arts, Epic Games, Microsoft, Nexon, Sony, Take-Two Interactive, Tencent, and Valve, this book forces us to rethink common misconceptions around the emergence of digital and mobile gaming. One Up is required reading for investors, creatives, managers, and anyone looking to learn about the major drivers of change and growth in contemporary entertainment.
Keywords: Business; Computer games; Video games